An examination of the nature and extent of linkages among milkfish hatcheries in Western Visayas. - Patriarca, Nedion L; Robles, John P. (2002.)
The present study examines the nature and extent of linkages among milkfish hatcheries in Western Visayas, identifies the factors that influence the nature and extent of linkages, and discusses how the nature and extent of linkages contributed to the present state of mlkfish fryindustry in the region. The findings of the study show that the link between the two sub-sectors (egg and fry producers under core-satellite arrangement) is very weak because of imperfections in the provision of services/assistance in the purchasing of input and output distribution. The failure of the core-satellite arrangement scheme to strengthen linkages among sub-sectors in the milkfish industry hampers the efforts of the government towards less dependence on the wild fry or fry imports. Linkages amon sub-sectors in the milkfish industry can be strengthened by fast tracking technology delivery, cost sharing, enforcement of contracts, and intensifying business relationships during the different sub-sectors.
Research Project (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Milkfish Hatcheries -- Western Visayas